TFPI2 promotes NK cell–mediated glioblastoma killing through adhesion and checkpoint control - Dongpeng Zheng; Fengqi Li; Zhuang Zhang; Yunyi Dong; Xuebin Zhang; Xueren Li; Jingyue Yang; Shouchun Peng; Budong Chen; Shupeng Sun; Zichuan Liu; Xin Mu (Proceedings of the National Academy of Sciences, 2026)
Immune-mediated killing triggers dynamic transcriptional adaptations in tumor cells that can reciprocally regulate the cytolytic process. Unraveling such feedback mechanisms is crucial for advancing cancer immunotherapy. Here, we identified tissue factor pathway inhibitor 2 (TFPI2) as a central node in natural killer (NK)–glioblastoma cross talk. Using transcriptomic and functional approaches, we demonstrated that NK cell attack induces TFPI2 expression in glioblastoma cells via IL1β- and TNFα-driven activation of NFκB signaling. TFPI2 not only restrains tumor proliferation by suppressing the POU2F2–CCND1 axis but also enhances NK cytotoxicity through two complementary mechanisms: It supports optimal ICAM1 expression to promote NK–tumor adhesion, and it selectively represses the immune checkpoint molecule SIGLEC15, restoring NK cell effector function. In vivo, loss of TFPI2 accelerates glioblastoma progression and abrogates the efficacy of adoptive NK cell therapy in a context-dependent manner; the functionality is likely restricted to tumors retaining the capacity for TFPI2 induction upon inflammatory stimuli. Our findings identified the TFPI2–ICAM1 and TFPI2–SIGLEC15 axes as conditional regulators of immune–tumor adhesion and checkpoint control, supporting TFPI2 as a candidate therapeutic target for a subset of glioblastomas amenable to inflammatory reprogramming.